The body digital : a brief history of humans and machines from cuckoo clocks to ChatGPT - Chang, Vanessa, 1969- (Melville House, 2025)
"A dazzling tour of the history of technology and its complex relationship to the human body. What is the relationship between our bodies and our senses and technology? In today's world of blinding technological change, of artificial intelligence and deepfakes and Chat GPT, it is easy to forget that we have always had complicated relations with technology--whether that technology is computers, player pianos, and even eyeglasses. In this wide-ranging and fascinating study, Vanessa Chang takes us on a historical tour of the interactions between our bodies and machines, showing that the advent of new technologies has always been met with varied reactions, from misplaced fear to tragic over-optimism. The result is cultural critique of the highest order and a profound demonstration of the eternal truth that in order to understand the future, we must look to the past."--